The response time to emotional stimuli (including facial expressions photos) during the fMRI scanning in affective disorders: mild and moderate depression and dysthymic disorder - M. Ye. Mel’nikov; D. D. Bezmaternykh; E. D. Petrovskiy; L. I. Kozlova; M. B. Shtark; A. A. Savelov; O. S. Shubina; K. A. Natarova (Бюллетень сибирской медицины)
Objective. Estimation of the response time and accuracy of emotional stimuli during the fMRI task fulfillment in participants suffering from mild to moderate depressive disorder or from dysthymic disorder.Materials and methods. 21 subjects with mild to moderate depressive disorder or dysthymic disorder (D) participated, and 21 healthy volunteers (H) matched by age and sex ratio were included in the control group.  In two fMRI paradigms subjects were observing photos of the faces with different emotional expressions. The first task was to guess the gender of the people on the screen, and the second one was to recognize the emotion experienced by the person in the photo. In the third paradigm participants were sorting different images into pleasant and unpleasant. The subjects responded by pressing one of two buttons. The response time and accuracy were the subjects of analysis.Results. On the most of the computed parameters patients with depressive disorder did not differ from controls. However, in the first paradigm these subjects demonstrated slower reaction to neutral (H = (1415 ± 408) ms,  D = (1 878 ± 850) ms; t = 2.25; p < 0,05) and disgusted (H = (1 183 ± 310) ms, D = (1 526 ± 646) ms; t = 2.20; p < 0.05) expressions, and greater standard deviations of the response time to disgusted (H = (219 ± 125) ms,  D = (675 ± 645) ms; t = 3.18; p < 0,01), happy (H = (445 ± 310) ms, D = (836 ± 579) ms; t = 2.73;  p < 0.05), surprised (H = (580 ± 438) ms, D = (1 043 ± 785) ms; t = 2.36; p < 0,05), and neutral  (H = (487 ± 416) ms, D = (895 ± 727) ms; t = 2.23; p < 0.05) faces. On the second stage group of participants with depressive disorder had greater standard deviation of the response time to disgusted portraits (H = (1 506 ± 1 273) ms, D = (2 168 ± 1 355) ms; U =131; p < 0.05). Moreover, subjects diagnosed with a depressive disorder less often chose the answer “happy” (H = (6,8 ± 1,1) ms, D = (6.0 ± 0.8) ms; U = 131; p < 0.05) while guessing the emotion in the photo.Conclusion. Participants diagnosed with mild to moderate depressive disorder or dysthymic disorder perform significantly slower than healthy ones during the “background” processing of the facial expressions and also tend to identify mimic as happy less often than controls while aiming to recognize the feelings of others. However, the role of these features in the progress of depressive disorders and their perspectives as diagnostic markers are subjects for further research.